Regular poles for spinor L-series attached to split Bessel models of GSp(4) - Rösner, Mirko; Weissauer, Rainer (Arxiv, 2017)
For irreducible smooth representations π of GSp(4,k) over a non-archimedean local field k, Piatetskii-Shapiro and Soudry have constructed an L-factor depending on the choice of a Bessel model. It factorizes into a regular part and an exceptional part. We determine the regular part for the case of split Bessel models.